Customer emotional regulation and relationship quality: Evidence from the banking industry. Issue 4 (December 2016) - Alnawas, Ibrahim; Altarifi, Shadi
Abstract The aim of this paper is twofold: first to examine the extent to which customer perceptions of employee deep/surface acting influence customer deep/surface acting; second to assess the degree to which customer deep/surface acting strengthens/weakens the level of relationship quality (RQ). Survey data were collected from (291) respondents from 13 banks located in Jordan. Two key findings emerged from the current study. First, when customers encountered authentic employees (i.e., deep acting), they were more likely to modify their internal feelings to match the required displays, and less likely to express unauthentic emotions. On the other hand, when customers encountered unauthentic emotions, they were less likely to express unauthentic emotions. Second, customer deep acting is found to be positively associated with relationship satisfaction, commitment, and trust, whereas customer surface acting is negatively associated with relationship satisfaction and trust. This study adds to the body of knowledge on the antecedents of RQ through identifying customer emotional regulation as a key determinant of that.